Technical sheet of influence of freeze-dried yeast starter cultures on volatile compounds of tchapalo, a traditional sorghum beer from Côte d’Ivoire - Hermann, COULIBALY Wahauwouélé; Jean-Paul, BOUATENIN Koffi Maizan; Alfred, KOUAME Kohi; Peggy, RIGOU (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2017)
The production of the Ivorian sorghum beer known as tchapalo remains more or less an empirical process. The use of starter cultures was therefore suggested as the appropriate approach to alleviate the problems of variations inorganoleptic quality and microbiological stability. In this study, we evaluated the capacity of S. cerevisiae and C. tropicalis to produce sorghum beer as freeze-dried starter in mixed or pure cultures. Beers produced with mixed freeze-dried cultures of S. cerevisiae F12-7 and C. tropicalis C0-7 showed residual sugars and ethanol contents similar to beers obtained with S. cerevisiae F12-7 pure culture, but the total sum of organic acids analyzed was the highest with the mixed culture (15.71 g/L). Higher alcohols were quantitatively the largest group of volatile compounds detected in beers. Among these compounds, 2-phenyl ethanol, a higher alcohol that plays an important role in beer ï¬‚avor, was highly produced with the mixed culture (10174.8 µg/L) than with the pure culture (8749.9 µg/L).